Relationship Between Nutritional Status And Degenerative Diseases In The Elderly - Anis Permanasari; Fitria Saftarina; Soedjarwo (International Journal of Health Engineering and Technology, 2023)
The increasing number of elderly population has resulted in an epidemiological transition, namely the shift in disease patterns from infectious diseases and nutritional disorders to degenerative diseases. The health of the elderly basically lies in their nutritional status. Nutritional problems in the elderly are mostly a problem of excess nutritional status which triggers the emergence of various degenerative diseases. Some of the diseases that are often experienced by the elderly include hypertension, arthritis, stroke, chronic obstructive pulmonary disease (COPD), and diabetes mellitus. The purpose of this study was to determine the relationship between nutritional status and degenerative diseases experienced by the elderly. This study uses a literature review method with a reference study approach. The keywords used in the journal search were "nutritional status, degenerative diseases, elderly". The number of articles included in the inclusion criteria was nine articles. Based on the results of a literature study, it is stated that the nutritional status of the elderly has an effect on the emergence of degenerative diseases. From the nine articles reviewed, it can be concluded that there is a relationship between nutritional status and degenerative diseases experienced by the elderly.